Anaemia and Family Income are associated with Preeclampsia Maternal Death in Jember District, Indonesia - Mergy Gayatri; Nurul Fathiyyah; Jesica Mulyadi; Diadjeng Setya Wardani; I Wayan Agung Indrawan (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2022)
Introduction: Preeclampsia is a pregnancy-related complication causing maternal morbidity and mortality. This study aimed to determine the relationship between anaemia and family income, and maternal death from preeclampsia in Jember district. Materials and Methods: Case-control, using medical maternal autopsy verbal, from January 2016 to December 2019. 43 mortality cases from preeclampsia, and 43 controls were included in this study. Chi-square test was to test the relationship between anaemia and family income, and maternal death from preeclampsia. Results: Mothers who died from preeclampsia were more likely to have anaemia (83.72%), and being low income (86.05%). Anaemia (OR 3.703, 95% CI p-value 0.009) and low income (OR 4.032, 95% CI, p –value 0.007) were associated with preeclampsia maternal mortality. Conclusions: To reduce the prevalence of death from preeclampsia, preventive measurement for anaemia during pregnancy should be undertaken. In addition, women with low income during pregnancy should be encouraged to have health insurance.